2020
DOI: 10.11591/eei.v9i3.1985
|View full text |Cite
|
Sign up to set email alerts
|

Quality and size assessment of quantized images using K-Means++ clustering

Abstract: In this paper, an amended K-Means algorithm called K-Means++ is implemented for color quantization. K-Means++ is an improvement to the K-Means algorithm in order to surmount the random selection of the initial centroids. The main advantage of K-Means++ is the centroids chosen are distributed over the data such that it reduces the sum of squared errors (SSE).  K-Means++ algorithm is used to analyze the color distribution of an image and create the color palette for transforming to a better quantized image compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The parameters used in the K-Means, GMM, and AHC algorithms were the number of clusters, and in this study the number of clusters was observed in the range of 2 to 50 clusters. K-means, AHC, and GMM are included in clusteringbased algorithms so that the selection of the number of clusters and the initial initialization of centroids greatly affect the results of clustering [35]. Based on the results obtained in Figure 4 to Figure 6, it can be concluded that the output of the PCA_2 with 2 features have the highest silhouette score using the K-means, GMM, and AHC algorithms, for all the number of clusters 2 to 50.…”
Section: Number Of Clusters Observation On K-means Gmm and Ahcmentioning
confidence: 95%
“…The parameters used in the K-Means, GMM, and AHC algorithms were the number of clusters, and in this study the number of clusters was observed in the range of 2 to 50 clusters. K-means, AHC, and GMM are included in clusteringbased algorithms so that the selection of the number of clusters and the initial initialization of centroids greatly affect the results of clustering [35]. Based on the results obtained in Figure 4 to Figure 6, it can be concluded that the output of the PCA_2 with 2 features have the highest silhouette score using the K-means, GMM, and AHC algorithms, for all the number of clusters 2 to 50.…”
Section: Number Of Clusters Observation On K-means Gmm and Ahcmentioning
confidence: 95%